EMPOWERING SPEAKING SKILLS THROUGH SPARKOL VIDEO SCRIBE: A CASE OF SMA STUDENTS (English Community Journal, 2022)
The objectives of this study were to find out whether or not there was a significant improvement in speaking skills by using Sparkol Video Scribe with Zoom Application and whether or not there was a significant difference in speaking skills between the tenth-grade students who were taught by using Sparkol Video Scribe with Zoom Application and those who were not. This research used a quasi-experimental design. The population of this study was the tenth grade of SMA LTI IGM Palembang. The paired sample t-test and independent sample t-test were used to analyze the hypotheses. The results showed that the students’ speaking skills of recount text were significantly improved after they were taught by using Sparkol Video Scribe, and there was a significant difference in speaking skills of recount text to the tenth-grade students who were taught by using Sparkol Video Scribe with zoom application and those who were not.